The Roles of Neutrophils in the Pathogenesis of Liver Diseases - Tang, Jiaojiao; Yan, Zijun; Feng, Qiyu; Yu, Lexing; Wang, Hongyang (Frontiers in Immunology, 2021)
Neutrophils are the largest population of circulating leukocytes and the first responder against invading pathogens or other danger signals. Sophisticated machineries help them play critical roles in immunity and inflammation, including phagocytosis, superoxide production, cytokine and chemokine production, degranulation, and formation of neutrophil extracellular traps (NETs). After maturation and release from the bone marrow, neutrophils migrate to inflamed tissues in response to many stimuli. Increasing evidences indicate that neutrophils are critically involved in the pathogenesis of liver diseases, including liver cancer, thus making them promising target for the treatment of liver diseases. Here, we would like to provide the latest finding about the role of neutrophils in liver diseases and discuss the potentiality of neutrophils as target for liver diseases.